Trends in Diurnal Cycle of Summertime Rainfall Over Coastal South China in the Past 135 Years: Characteristics and Possible Causes. Issue 8 (26th April 2021) - Su, Lin; Fung, Jimmy C. H.; Li, Junlu; Wong, Wai Kin
Abstract: The interdecadal changes in the diurnal cycle of summertime rainfall over coastal South China (CSC) were analyzed for the period of 1884–2018. The results revealed that rainfall intensity has increased with the decrease of occurrence frequency during both pre‐ and mid‐summer in the past 135 years. During the most recent 40 years, occurrence frequency and intensity of nocturnal rainfall, especially extreme rainfall, have substantially increased over CSC, whereas those of daytime extreme rainfall have decreased. Different increasing rates of near‐surface temperature over land and sea are the main contributors to the distinct trends of daytime and nocturnal extreme rainfall. During daytime, a higher increasing rate of near‐surface temperature over sea results in a smaller temperature gradient along the coast, leading to a less convective atmosphere. This negates the effect of increased air‐temperature over CSC in both pre‐ and mid‐summer. In contrast, during nighttime, a higher increasing rate of near‐surface temperature over sea results in a greater temperature gradient along the coast, leading to stronger low‐level offshore winds and more convective layers over coastal waters. During pre‐summer, the stronger nocturnal low‐level offshore winds meets the warm and moist monsoonal flows, substantially enhancing nocturnal extreme rainfall along the coast. In mid‐summer, more vigorous upward motions over coastal waters of CSC enhance convective activities during nighttime, which also lead to an intensification of nocturnal rainfall. The most significant increase and intensification of extreme rainfall is observed in western CSC during pre‐summer, where the land‐sea difference of near‐surface temperature is the greatest over CSC. Key Points: Diurnal cycle of rainfall over coastal South China during summertime from 1884 to 2018 were analyzed Different from the 135‐year trend, daytime and nocturnal rainfall, especially extreme rainfall, exhibits distinct trends during 1979–2018 Different rates of near‐surface temperature over land and sea contribute to the distinct trends of daytime and nocturnal extreme rainfall